Corporate Social Responsibility & Profitability in South Africa - Ndlovu, Nkamogeleng (Graduate School of Business (GSB), 2024)
Corporate Social Responsibility (CSR) has been widely studied for numerous decades. In particular, researchers have been keenly interested in its relationship to firm financial performance. However, only recently have measurable and standardised tools been established to quantify CSR, through the creation of Environmental, Social and Governance (ESG) ratings methodologies and scorecards. Investors globally are using ESG integration to help inform investment decisions, thus CSR is no longer a nice-to-have, but a must-have for those companies that wish to participate in the global investment and capital markets space. South African companies are no exception. As South Africa is one of the largest economies in Africa, South African listed equities provide an avenue for international investment into the continent. As such, CSR and the measurement thereof is important for South African companies to not only attract, but to retain, global investments. This study examines the impact of CSR on profitability of listed firms on the Johannesburg Stock Exchange (JSE). The study analyses panel data from 2016 to 2019 using the multiple regression panel data model, applying fixed, random and GMM estimation approaches. From the analysis, the study finds a positive relationship between Return on Assets (ROA), Market-to-Book (MKTBK) and aggregate CSR. However, upon assessment of the individual CSR variables and their relationship with financial performance, results are either positive or negative, supporting the existing body of research, which, on balance, yields inconclusive results. In conclusion, it is recommended that the government creates an environment that is conducive for the achievement of CSR ambitions for firms. The adoption of CSR practices is beneficial for all stakeholders and it is incumbent upon the government to facilitate companies' endeavours. As the proliferation of ESG continues, South African companies will no longer have the luxury of choice with respect to adopting CSR policies.